High-resolution measurements of atmospheric molecular hydrogen and its isotopic composition at the West African coast of Mauritania - S. Walter; A. Kock; T. Röckmann (Biogeosciences, 2013)
Oceans are a net source of molecular hydrogen (H2) to the atmosphere, where nitrogen (N2) fixation is assumed to be the main biological production pathway followed by photochemical production from organic material. The sources can be distinguished using isotope measurements because of clearly differing isotopic signatures of the produced hydrogen. Here we present the first ship-borne measurements of atmospheric molecular H2 mixing ratio and isotopic composition at the West African coast of Mauritania (16–25° W, 17–24° N). This area is one of the biologically most active regions of the world's oceans with seasonal upwelling events and characterized by strongly differing hydrographical/biological properties and phytoplankton community structures. The aim of this study was to identify areas of H2 production and distinguish H2 sources by isotopic signatures of atmospheric H2. For this more than 100 air samples were taken during two cruises in February 2007 and 2008. During both cruises a transect from the Cape Verde Islands towards the Mauritanian Coast was sampled to cover differing oceanic regions such as upwelling and oligotrophic regimes. In 2007, additionally, four days were sampled at high resolution of one sample per hour to investigate a possible diurnal cycle of atmospheric H2. Our results indicate the influence of local sources and suggest the Banc d'Arguin as a pool for precursors for photochemical H2 production, whereas oceanic N2 fixation could not be identified as a source for atmospheric H2 during these two cruises. The variability in diurnal cycles is probably influenced by released precursors for photochemical H2 production and also affected by a varying origin of air masses. This means for future investigations that only measuring the mixing ratio of H2 is insufficient to explain the variability of an atmospheric diurnal cycle and support is needed, e.g. by isotopic measurements. Nevertheless, measurements of atmospheric H2 mixing ratios, which are easy to conduct online during ship cruises, could be a useful indicator of production areas of biological precursors such as volatile organic compounds (VOCs) for further investigations.